Morphological effects of mesenchymal stem cells and pulsed ultrasound on condylar growth in rats: a pilot study - Oyonarte Rodrigo; Becerra Daniela; Díaz-Zúñiga Jaime; Rojas Victor; Carrion Flavio (Sciendo, 2013)
Aim: The aim of this study was to assess and describe the morphological effects of an intra-articular injection of Mesenchymal Stem Cells (MSCs) and/or Low Intensity Pulsed Ultrasound (LIPUS) stimulation on the mandibular condyles of growing rats, using cone beam computed tomography (CBCT) and histology.